Miniaturization of Implantable Antenna in ISM Band for Biomedical Applications - Rajiv Kumar Nehra; Sourabh Rana; Vaani Sharma (Journal of Power Electronics and Devices, 2018)
Three shorting pins are used for miniaturization purposes, directly connecting the patch to the ground plane. Thus, a compact size of 90 mm x 90 mm x 25.27mm is obtained. HFSS software is used to showcase the antenna design along with the requisite parameters like resonating frequency, reflection coefficient and current distribution. By changing the coaxial feeding length with respect to λg, value of reflection coefficient is improved. As a result, resonant frequency of 2.38GHz and reflection coefficient of -19.5dB are obtained. Roger RO3210 is used as a substrate and superstrate material.